Mathematical and geoinformation modeling of snowmelt process in the river drainage basins of the Kama region - V. G. Kalinin; A. A. Shaydulina; V. S. Rusakov; M. A. Fasakhov (Лëд и снег)
The paper studies the patterns and snowmelt regime on the case of several river catchments of the Kama Region. Based on the temperature coefficient method, detailed digital maps and GIS-technologies, a model of spring snow melting has been developed. This model makes it possible to take into account the spatial distribution of meteorological information, features of the relief and soil-vegetation cover more accurately. The estimation of the slope aspect influence on the spring snow melting processes by means of correction coefficients and the technique of determining their optimal values is proposed. A method for verifying the results of calculations of the snow cover spatial distribution based on space monitoring data is proposed. To perform a quantitative comparison of model maps with interpreted images, the choice of the value of the fraction of remaining snow in each cell of the map (information on the presence or absence of snow cover) was justified. If the value of fraction ≥ 0.5, then 1 is assigned – snow is present, if < 0.5, then 0 is assigned – no snow. The simulation results of snow melting for the Kosa–Kosa catchment area during the spring periods of 2004, 2010 and 2015 showed that the average overlap of snow-covered area on the model maps and decoded satellite images is 73.67%. Validation of the proposed snowmelt model was carried out in the Kama–Gainy and the Vishera–Ryabinino catchments. The average overlap area between the model maps and interpreted satellite images was 72.56 and 88.56%, respectively.